Analysis of foodborne disease surveillance of geriatrics from 2018 to 2022 in China’s Mainland - FAN Penghui; ZHANG Ronghua; HUO Xiang; LIN Li; JIANG Yuyan; MA Xiaochen; LIU Hong; LIU Zhitao; CHU Zunhua; LIANG Jinjun; HU Qingwen; LIU Jikai; et al. (Zhongguo shipin weisheng zazhi)
ObjectiveTo provide scientific basis for the prevention and control of foodborne diseases among the geriatrics in China’s Mainland， the epidemiological characteristics of foodborne diseases was understood.MethodsInformation on acute gastroenteritis cases aged ≥65 years in China’s Foodborne Disease Case Surveillance System from 2018 to 2022 was collected and analyzed.ResultsThe overall prevelance of foodborne disease monitoring pathogens among the geriatrics in China was 9.15% （7 218/78 904， 95%CI： 8.95%， 9.35%， with Salmonella spp. being the highest （4.90%， 3 860/78 699， 95%CI： 4.75%， 5.06%）， Norovirus （2.07%， 1 517/73 173， 95%CI： 1.97%， 2.18%）， Diarrheogenic E. coli （1.39%， 1 015/72 763， 95%CI： 1.31%， 1.48%）， Vibrio parahaemolyticus （1.00%， 782/78 386， 95%CI： 0.93%， 1.07%） and Shigella spp. （0.19%， 147/78 611， 95%CI： 0.16%， 0.22%）. The prevelance of Salmonella spp. in male elderly was higher than that in female， while the prevelance of Vibrio parahaemolyticus in female was higher than that in male. The higher the age， the lower the prevelance was. Geriatrics with foodborne diseases had obvious seasonality. The prevelances of Salmonella spp.， Shigella spp.， Vibrio parahaemolyticus and diarrheogenic E. coli reach their peak in July and August， while Norovirus reaches its peak in February and March. The overall prevelance varies across different regions of the country， and the differences are statistically significant （χ²=546.85， P<0.001）. The categories of suspicious exposed foods mainly include meat and meat products， grains and its products， vegetables and its products， etc， with households being the main place of consumption.ConclusionSalmonella spp. has the highest prevelance in active surveillance of acute gastroenteritis among the geriatrics in China’s Mainland. The epidemiological characteristics of surveilled pathogens vary in different gender， age and regions， taking targeted measures should be formulated based on the corresponding distribution of characteristics to prevent foodborne diseases in geriatrics.